Fintech: Pengaruh teknologi finansial (fintech) terhadap sistem perbankan pada tahun 2024 - Ramadhani, Miagasela Aprilia (Maliki Interdisciplinary Journal, 2024)
This research examines the impact of financial technology (Fintech) on the banking system in 2024. Fintech has grown rapidly in recent years, bringing innovations that are changing the way financial services are provided and accessed by consumers. This study highlights the impact of Fintech on operational efficiency, business models and risks faced by traditional banks. Key findings show that Fintech is driving banks to increase the digitalization of services, adopt new technologies such as blockchain and artificial intelligence, and expand the reach of financial inclusion. Additionally, collaboration between banks and Fintech companies is increasing, enabling the creation of a more integrated and responsive financial ecosystem. However, significant challenges have also emerged, including cybersecurity issues, evolving regulations, and the need to increase digital literacy among consumers. This research concludes that the success of the Fintech era banking system is highly dependent on the bank's ability to adapt quickly to changes in technology and market needs, while maintaining customer trust and security. Thus, banks that successfully transform digitally will have a stronger position in the future financial landscape. This research is important for providing a deeper understanding of the dynamics between Fintech and the banking system, as well as providing guidance for policymakers and industry leaders in formulating effective strategies to face challenges and exploit emerging opportunities.